The Academic Article in an Age of Mechanical Production or Reproduction*. Issue 1 (2nd January 2017) - Chapman, Michael
Abstract : At a time in which university managerialism increasingly pressurises academics to publish or perish, has mechanical production or reproduction (including "self-plagiarism"), become the norm of the academic article? Or, is it that journal convention itself discourages the power to think and write differently? And is the journal of the South, at least in the humanities, exempt from what is a northern institutional imposition of purpose, shape and style?